Modelling Recurrence Motion on a Large Volume Semi-Submersible - Putra, Risandi Dwirama; Koto, J. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
This research described a study of recurrence motion on a volume submersible. Recurrence is the phenomenon in which a system of quasi-periodically returns to its initial conditions after undergoing some degree of evolution, this finding supports the theory of quasi determinism (QD) of sea waves. The research to determine recurrence characteristic of motion in the large volume of semisubmersible using computational methods of ANSYS® AQWA™. The motion was analyzed four types of different incident waves by using JONSWAP Spectrum and are generally regarded as a pure randomness in nature which interacts with the structure generating hydrodynamic motion. Responses of motion were performed for 3 hours, in which it was divided into 9 seed for each incident wave. Hs 7 meters Tp 12.7 sec, Hs and 7 meters Tp 13.5 sec, Hs 8 meters and Tp 12.7 sec, and Hs 8 meters and Tp 12.7 sec , recurrence occurred in the interval (to +635s, to +879) - (to+1774, +to2074), (to +1460, to+1635) - (to +5758, to +5933), (to +693, to+882) - ( to+1735, to+1924) and (to +792, to+992) - (to+1938, to+2138), respectively. Recurrence motion on a large volume semisubmersible support the to support the quasi determinism (QD) theory.